Evolving the Design of a Mobile Application to Support Transition to Tertiary Education - Zhao, Yu; Pardo, Abelardo (Frontiers in ICT, 2017)
Students’ transition to tertiary education plays a critical role in their overall post-secondary experience. Even though educational institutions have designed and implemented various transition support programs, most of them still struggle to collect detailed information and provide tailored and timely support to students. With the high adoption rate of smart phones among university students, mobile applications can be used as a platform to provide personalized support throughout the transition, which has the potential to address the shortcomings of existing programs. Moreover, the use of mobile applications to support the transition to tertiary education can benefit from emerging techniques to design applications to support individuals through transition processes. In this paper, we present the design and development process of myUniMate, a mobile application that allows students to track and reflect on information from multiple aspects of their university lives. The paper describes the user-centered design approach used in the design, the implementation process, and how the initial version evolved based on our previous study. We conducted a 4-week field trial with first year university students to validate our design.